2015
DOI: 10.1073/pnas.1509777112
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of ozone damage to historical maize and soybean yields in the United States

Abstract: Numerous controlled experiments find that elevated ground-level ozone concentrations ([O3]) damage crops and reduce yield. There have been no estimates of the actual yield losses in the field in the United States from [O3], even though such estimates would be valuable for projections of future food production and for cost–benefit analyses of reducing ground-level [O3]. Regression analysis of historical yield, climate, and [O3] data for the United States were used to determine the loss of production due to O3 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
127
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 177 publications
(149 citation statements)
references
References 37 publications
6
127
1
Order By: Relevance
“…This was accompanied by greater SLA, indicating reduced leaf mass per unit area, which often is associated with lower photosynthetic capacity and/ or lower starch content (Poorter et al, 2012). This is consistent with the accelerated leaf senescence at elevated [O 3 ] observed in other species (Miller et al, 1999;Ainsworth et al, 2012;Gillespie et al, 2012) and with reduced carbon gain being at least partly responsible for the 10% reduction in yield of U.S. maize due to O 3 over the last 30 years (McGrath et al, 2015). This study also showed that, using hyperspectral reflectance, it was possible to detect genotypic differences in physiological and biochemical leaf traits across maize lines and variation in their response to elevated [O 3 ] (Fig.…”
Section: High-throughput Phenotyping Of the Stress Response In Maizesupporting
confidence: 75%
“…This was accompanied by greater SLA, indicating reduced leaf mass per unit area, which often is associated with lower photosynthetic capacity and/ or lower starch content (Poorter et al, 2012). This is consistent with the accelerated leaf senescence at elevated [O 3 ] observed in other species (Miller et al, 1999;Ainsworth et al, 2012;Gillespie et al, 2012) and with reduced carbon gain being at least partly responsible for the 10% reduction in yield of U.S. maize due to O 3 over the last 30 years (McGrath et al, 2015). This study also showed that, using hyperspectral reflectance, it was possible to detect genotypic differences in physiological and biochemical leaf traits across maize lines and variation in their response to elevated [O 3 ] (Fig.…”
Section: High-throughput Phenotyping Of the Stress Response In Maizesupporting
confidence: 75%
“…stratosphere-troposphere exchange | surface ozone | National Ambient Air Quality Standard | radioactive isotope of sulfur | Santa Ana wind H igh ground-level ozone (O 3 ) mixing ratios exert adverse impacts on human health, vegetation, and materials (1,2). In the free troposphere, O 3 is an important greenhouse gas contributing to global warming.…”
mentioning
confidence: 99%
“…In the United States, the impact of O 3 -induced crop damage was observed for maize and soybean from 1980 to 2011. They showed that over that period production of rain-fed fields of soybean and maize were reduced by roughly 5% and 10%, respectively, costing approximately 9 billion USD annually (McGrath, Betzelberger et al, 2015).…”
Section: Economic Impact Of Air Pollutionmentioning
confidence: 99%